Factors Influencing Plagiarism Among Faculty Members and Research Scholars in the Higher Education System - Salauddin, Dr Nazia (DESIDOC Journal of Library & Information Technology, 2023)
Plagiarism considered serious academic misconduct and a violation of academic integrity and ethics. This study identified users' perceptions and attitudes about plagiarism and strategies for prohibiting in academia and found out the potential causes of plagiarism among higher education systems. The survey method used stratified random sampling techniques to make the strata for the study population, 213 data collected from scholars and faculty members. The survey result demonstrates the primary cause of plagiarism appearance and how different plagiarism indicators have been evaluated within the primary causes. The findings show that information and communication technology, specifically responsible for two factors, easiness of copying and availability of access to resources and new technologies, has a substance responsible for plagiarism. The primary purpose of the study of academic fraternity must transmit learning skills and knowledge. The intention based on ethical principles resulting from its misconduct, and plagiarism is just exploitation for an academic career. Academicians can significantly contribute to the correct set of skills to prevent students from plagiarizing, independently of the student's experiences.